Anti-apoptotic signaling as a cytoprotective mechanism in mammalian hibernation - Andrew N. Rouble (PeerJ, 2013)
In the context of normal cell turnover, apoptosis is a natural phenomenon involved in making essential life and death decisions. Apoptotic pathways balance signals which promote cell death (pro-apoptotic pathways) or counteract these signals (anti-apoptotic pathways). We proposed that changes in anti-apoptotic proteins would occur during mammalian hibernation to aid cell preservation during prolonged torpor under cellular conditions that are highly injurious to most mammals (e.g. low body temperatures, ischemia). Immunoblotting was used to analyze the expression of proteins associated with pro-survival in six tissues of thirteen-lined ground squirrels, Ictidomys tridecemlineatus. The brain showed a concerted response to torpor with significant increases in the levels of all anti-apoptotic targets analyzed (Bcl-2, Bcl-xL, BI-1, Mcl-1, cIAP1/2, xIAP) as well as enhanced phosphorylation of Bcl-2 at S70 and T56. Heart responded similarly with most anti-apoptotic proteins elevated significantly during torpor except for Bcl-xL and xIAP that decreased and Mcl-1 that was unaltered. In liver, BI-1 increased whereas cIAP1/2 decreased. In kidney, there was an increase in BI-1, cIAP and xIAP but decreases in Bcl-xL and p-Bcl-2(T56) content. In brown adipose tissue, protein levels of BI-1, cIAP1/2, and xIAP decreased significantly during torpor (compared with euthermia) whereas Bcl-2, Bcl-xL, Mcl-1 were unaltered; however, Bcl-2 showed enhanced phosphorylation at Thr56 but not at Ser70. In skeletal muscle, only xIAP levels changed significantly during torpor (an increase). The data show that anti-apoptotic pathways have organ-specific responses in hibernators with a prominent potential role in heart and brain where coordinated enhancement of anti-apoptotic proteins occurred in response to torpor.